Role of a cyclopentadienyl ligand in a heteroleptic alkoxide precursor in atomic layer deposition - Yoon, Hwi; Lee, Yujin; Lee, Ga Yeon; Seo, Seunggi; Park, Bo Keun; Chung, Taek Mo; Oh, Il Kwon; Kim, Hyungjun (Journal of Chemical Physics, 2024)
Alkoxide precursors have been highlighted for depositing carbon-free films, but their use in Atomic Layer Deposition (ALD) often exhibits a non-saturated growth. This indicates no self-limiting growth due to the chain reaction of hydrolysis or ligand decomposition caused by β-hydride elimination. In the previous study, we demonstrated that self-limiting growth of ALD can be achieved using our newly developed precursor, hafnium cyclopentadienyl tris(N-ethoxy-2,2-dimethyl propanamido) [HfCp(edpa)3]. To elucidate the growth mechanism and the role of cyclopentadienyl (Cp) ligand in a heteroleptic alkoxide precursor, herein, we compare homoleptic and heteroleptic Hf precursors consisting of N-ethoxy-2,2-dimethyl propanamido (edpa) ligands with and without cyclopentadienyl ligand—hafnium tetrakis(N-ethoxy-2,2-dimethyl propanamido) [Hf(edpa)4] and HfCp(edpa)3. We also investigate the role of a Cp ligand in growth characteristics. By substituting an alkoxide ligand with a Cp ligand, we could modify the surface reaction during ALD, preventing undesired reactions. The last remaining edpa after Hf(edpa)4 adsorption can undergo a hydride elimination reaction, resulting in surface O-H generation. In contrast, Cp remains after the HfCp(edpa)3 adsorption. Accordingly, we observe proper ALD growth with self-limiting properties. Thus, a comparative study of different ligands of the precursors can provide critical clues to the design of alkoxide precursors for obtaining typical ALD growth with a saturation behavior.
Keywords: Alkoxide precursor; Atomic-layer deposition; Carbon-free; Chain reaction; Cyclopentadienyl ligands; Cyclopentadienyls; Free films; Heteroleptic; Hydride elimination; Self-limiting growths